Exploring the Dynamic Capabilities Pattern in Small and Medium-sized Enterprises (MSMEs): A Phenomenological Study of MSME stagnancy in Indonesia - Agustina Shinta Mariani; Arief Rakhman; Edward Widjojokusumo; Glenny Soetanto; Johnson Leonardi (Jurnal Syntax Admiration, 2024)
The objective of this research is to explore the Dynamic Capability Pattern, furthermore to observe how motivational and sociological factors impact the occurrence of stagnancy of MSMEs in Indonesia. Design/Methodology/Approach – A qualitative approach is applied with Open Questions Interviews towards 10 (ten) MSME actors in Indonesia who represent a range of industries including food and beverage, fashion retail, and the chemical raw materials sector The findings of this study underscore several key points: SMEs consistently exhibit dynamic capabilities, particularly in the stages of sensing and seizing opportunities, however they frequently encounter challenges when striving to advance to a transformational stage. Continuous engagement in sensing and seizing cycles is crucial for MSMEs to prosper and progress to the next level of development. However, underdeveloped SMEs encounter challenges in re-engaging these cycles effectively. Mentorship from experienced communities or business groups can enhance SMEs' willingness and ability to pursue further development. Motivational and sociological factors play a significant role in influencing dynamic capabilities within Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Research Limitations - As a qualitative study, this research used a limited sample of participants from the Food & Beverage, and Fashion retail sectors to acquire insights. Therefore, it is highly recommended that future research be conducted on a larger scale, involving a more diverse range of participants from various business sectors, to validate the cyclical patterns and factors influencing the Dynamic Capabilities of MSMEs in Indonesia. To the best of the author's understanding and knowledge, employing a qualitative approach in this research marks an early effort to thoroughly comprehend the consistency of Dynamic Capability Pattern, motivational and sociological forces that shape the decisions of MSMEs regarding their potential transformation.